MANAJEMEN SUMBER DAYA MANUSIA DI PERPUSTAKAAN EL-HAYAAH MADRASAH ALIYAH NEGERI 1 PEKANBARU - Gunawan, Agus; Lorenza, Saddam; Sandikaduana, Fangki (STKIP Pesisir Selatan, 2026)
This study aims to describe human resource management at the El-Hayaah Library of MAN 1 Pekanbaru, focusing on four main aspects: planning, recruitment and selection, training and development, and performance evaluation of librarians. A descriptive qualitative approach was used, with data collected through interviews, observation, and documentation. The results show that librarian planning is carried out contextually by considering institutional needs and internal competencies. The recruitment and selection process is directed toward meeting qualifications and librarian involvement in literacy programs, although it has not yet adopted an open system. Training and development are conducted gradually through internal activities and external training, particularly in improving information technology competencies. Performance evaluation is still conducted informally but considers discipline, work responsibility, and contributions to literacy programs. The study concludes that HR management at the library has been implemented adaptively and effectively, although it still requires a more structured, professional system based on national standards